The Framework Catalogue of Digital Competences - Jasiewicz, Justyna; Filiciak, Mirosław; Mierzecka, Anna; Śliwowski, Kamil; Klimczuk, Andrzej; Kisilowska, Małgorzata; Tarkowski, Alek; Zadrożny, Jacek (2015)
Abstract: Operational Programme Digital Poland - "Priority axis III: Digital competences of the society" focuses on raising digital activity in order to allow fully use possibilities of high-speed Internet and new public e-services. It comprises four actions including Training activities for development of digital competences with allocation of 180 mln PLN (divided into two competitions dedicated to NGOs). The point of reference for all the projects of the axis III is a document named The framework catalogue of digital competences. An important assumption of the catalogue is the connection between the digital competences and the users' needs and the benefits that they may gain in the key areas of life. The document, commissioned by the Ministry of Administration and Digitization, is of vital importance in the implementation of the new model in recognizing digital competences- the relational model